2023
DOI: 10.1186/s43141-023-00514-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization, characterization, comparison of self-assembly VLP of capsid protein L1 in yeast and reverse vaccinology design against human papillomavirus type 52

Moh Egy Rahman Firdaus,
Apon Zaenal Mustopa,
Nurlaili Ekawati
et al.

Abstract: Background Vaccination is the one of the agendas of many countries to reduce cervical cancer caused by the Human papillomavirus. Currently, VLP-based vaccine is the most potent vaccine against HPV, which could be produced by a variety of expression systems. Our study focuses on a comparison of recombinant protein expression L1 HPV52 using two common yeasts, Pichia pastoris and Hansenulapolymorpha that have been used for vaccine production on an industrial scale. We also applied bioinformatics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…However, the copy number is not necessarily proportional to the protein titer. 12 Moreover, recombinant protein overexpression might be damaging to host cell development and cause protein burden, which impacts protein production. 23 , 24 Meanwhile, HIP (Hansenula Integration Plasmid) which possesses an expression cassette was stably integrated into the genome of H. polymorpha and constantly expressed HPV type 52 L1 protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the copy number is not necessarily proportional to the protein titer. 12 Moreover, recombinant protein overexpression might be damaging to host cell development and cause protein burden, which impacts protein production. 23 , 24 Meanwhile, HIP (Hansenula Integration Plasmid) which possesses an expression cassette was stably integrated into the genome of H. polymorpha and constantly expressed HPV type 52 L1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…The genome was prepared with an amount of 5 ng and amplified for 40 cycles using specific primers with three-step amplification. 12 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers showed that self-assembled VLP formation and stable integration during protein induction were successful in both yeasts. These expression systems are used for vaccine production in the industry; however, the production effectiveness of desired proteins differs among yeasts [ 59 ].…”
Section: Yeast and Their Use For The Production Of Vlpsmentioning
confidence: 99%
“…HPV infects epithelial cells involving the skin, respiratory mucosa, or genital tract. High-risk HPV is the type of HPV that causes malignant tumors to lead to cancer containing HPV 16,18,31,33,45,51,and 52 [7]. Data from the Agency for Health Research and Development, Indonesian Ministry of Health, reported that HPV has the highest prevalence in Indonesia, namely HPV 16, 18, and 52, where HPV type 52 is a highrisk HPV with the highest percentage of 18.5% [8].…”
Section: Introductionmentioning
confidence: 99%